Anglo-Saxon Advertising: The Search for Sound - Allen, Matthew (2018)
Anglo-Saxon poetry may seem quite distant to English language learners; however, it all depends on the purpose for which it is used in the classroom. In the activity described in this article, students are asked to listen carefully to the sound of spoken words, and then apply two powerful patterns of discourse in their writing: alliteration and alternation; this after reading and debating examples. Created by intuition and need, and developed through trial and error, Anglo-Saxon Advertising quickly became a cornerstone of the introductory British literature course for university students of English as a second language (ESL). As a further part of the process of applying this teaching tool, it was found that this type of classroom activity is supported by current international research on the didactics of English as a second language (Boers, Lindstromberg & Eyckmans, 2012; Eyckmans & Lindstromberg, 2017).  In retrospect, the use of stimulating traditional literature in an English as a Second Language teaching environment raises fundamental questions about the importance of creativity in the classroom (Tsui, 2003), the need for a contemporary curriculum (Xie, 2014), the combination of language and literature (Zitlow, 2004), and the use of multiple modes of instruction (Traore & Kyei-Blankson, 2011)...